Chironomid pupal exuviae communities support the “field of dreams” hypothesis after the riparian vegetation recovery in headwater urban streams - Hugo H.L. Saulino; Miguel Cañedo-Argüelles; Susana Trivinho-Strixino; Guilherme Rossi Gorni; Juliano José Corbi (Ecological Indicators, 2021)
The biodiversity of headwater streams is gradually degrading as a result of urbanization. Although not always successful, ecosystem restoration can be useful in reversing such kind of degradation. In this study, chironomid pupal exuviae (Diptera) were be used as an indicator of riparian vegetation recovery success in the urban headwater streams of the Cerrado biome. Based on the “field of dreams” hypothesis, it was predicted that chironomid communities would significantly respond to this vegetation recovery through the colonization of urban habitats. Chironomids were collected using the surface-floating pupal exuviae technique in 10 urban and 10 reference sites (n = 60) during the dry season. The streams were characterized with the help of variables such as the Riparian Channel and Environmental Inventory (RCE) protocol, pH level, dissolved oxygen, depth, width of stream channel, flow velocity, land use composition, and the time elapsed after the vegetation in the streams were restored and measured. The urban headwater sites were wider and had a higher stream flow velocity owing to the bank erosion process, which resulted in low RCE scores. There weren’t any differences in the total taxa richness, abundance, beta diversity, and community composition between the urban and the reference sites. In urban streams, chironomid abundance was significantly and positively associated with the width and depth of the stream channel. Taxa richness responded positively to the physical and biological condition of the stream habitat (i.e., the sum of RCE scores), whereas turnover (beta diversity) responded significantly and negatively to land use. According to the indicator species analysis, different taxa richness was associated with each type of site, Pentaneura in urban, while Stenochironomus and Stempellinella in reference sites. The pool species of local streams and the recovery of vegetation through restoration (which improves habitat heterogeneity) were important factors in recovering the chironomid communities.